Alois Alzheimer and vascular brain disease: Arteriosclerotic atrophy of the brain - Engelhardt,Eliasz (2015)
Alois Alzheimer is best known for his description of neurofibrillary changes in brain neurons of a demented patient, identifying a novel disease, soon named after him by Kraepelin. However, the range of his studies was broad, including vascular brain diseases, published between 1894 and 1902. Alzheimer described the clinical picture of Arteriosclerotic atrophy of the brain, differentiating it from other similar disorders. He stated that autopsy allowed pathological distinction between arteriosclerosis and syphilis, thereby achieving some of his objectives of segregating disorders and separating them from syphilis. His studies contributed greatly to establishing the key information on vascular brain diseases, predating the present state of knowledge on the issue, while providing early descriptions of what would be later regarded as the dimensional presentation of the now called "Vascular cognitive impairment", constituted by a spectrum that includes a stage of "Vascular cognitive impairment not dementia" and another of "Vascular dementia".